Prolegomena to a Critical Grammar - Schächter, Josef. author. aut Link
XXII, 166 p.
Keywords: This book is the first English version of Prolegomena zu einer kritischen Grammatik, published by Julius Springer, Vienna, 1935, as Volume 10 of the Vienna Circle's series Schriften zur wissenschaftlichen Weltauffassung. The prefatory remarks of both editor and author acknowledge the influence ofWittgenstein in a general way. However, in aim and approach, the work differs from Wittgenstein's Philosophische Grammatik (l969). This is indeed based on material going back to 1932, some of which Schachter must have known. On the other hand, the present Prolegomena not only explains the general, philosophical principles to be followed, but in the light of these proceeds to cover the entire range of conventional grammar, showing where that is uncritical. Whether Wittgenstein in his turn knew of Schachter's work has never been explored. Schachter's object is universal grammar. As is natural, the examples in the original are largely drawn from German grammar, with occasional minor excursions into other languages. For English readers, what matters are the general problems of grammar: there is no point in tying these to the linguistic peculiarities of German, let alone a local variety of it. One who can grasp German at that level might as well read the original. The translation is therefore twofold: the text as a whole has been rendered into English, and the entire apparatus of examples has been replaced, as far as this can be done, by illustrations from English grammar, chosen so as to bring out the same kinds of problem as in the original.